2016
DOI: 10.1371/journal.pone.0161776
|View full text |Cite
|
Sign up to set email alerts
|

Micronized Organic Magnesium Salts Enhance Opioid Analgesia in Rats

Abstract: PurposeAs previously reported, magnesium sulphate administered parenterally significantly increased an opioid antinociception in different kinds of pain. Since the typical form of magnesium salts are poorly and slowly absorbed from the gastrointestinal tract we examined whether their micronized form could increase opioids induced antinociception.MethodsIn behavioural studies on rats morphine, tramadol and oxycodone together with magnesium (lactate dihydrate, hydroaspartate, chloride) in micronized (particles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…It is worth noting that magnesium ions [Mg 2+ ] belong to the class of physiological antagonists of NMDA receptors [3,4]. Results of own studies and the literature data demonstrated that Mg 2+ increased opioid analgesia in experimental animal models of neuropathic [5][6][7], inflammatory [5], as well as acute [8][9][10] pain. Furthermore, the results of several clinical trials confirmed that parenterally administered Mg 2+ reduces opioid consumption and improves postoperative pain scores without increasing opioid side effects [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that magnesium ions [Mg 2+ ] belong to the class of physiological antagonists of NMDA receptors [3,4]. Results of own studies and the literature data demonstrated that Mg 2+ increased opioid analgesia in experimental animal models of neuropathic [5][6][7], inflammatory [5], as well as acute [8][9][10] pain. Furthermore, the results of several clinical trials confirmed that parenterally administered Mg 2+ reduces opioid consumption and improves postoperative pain scores without increasing opioid side effects [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Today optimalized dosage forms in comparison to old standard ones can even double the bioavailability of a certain compound [61,62]. Or micronization, for example, can also dramatically improve the absorption [63].…”
mentioning
confidence: 99%